Actinomycosis - forgotten disease as a diagnostic challenge - Patrycja Łanowy; Krystian Ślusarz; Weronika Pyka; Jakub Dzindzio; Miłosz Bichalski; Maria Blaszkowska; Barbara Oczko-Grzesik; Jerzy Jaroszewicz (Kazimierz Wielki University, 2019)
Actinomycosis is neglected, an uncommon disease caused by bacteria. The greatest difficulty in correct and early diagnostics of actinomycosis is the fact that it often mimics other conditions. The difficulties in diagnostic of actinomycosis result in misdiagnosis, lengthening the patient's treatment time, unnecessary surgical treatment and sometimes dangerous complications. Aim of the article: The aim of the article is to familiarize readers with the rarest conditions that have been mistaken for actinomycosis.